Bibliometrics and semantics in XXI century Chilean social science journals - Díaz Herrera , Claudio; Moyano Díaz, Emilio (Revista General de Información y Documentación, 2023)
In the understanding that an area of study is configured according to the communication of its means of scientific dissemination in a given social, political and economic context, the article aims to analyze the semantics and bibliometric structure contained in miscellaneous Chilean scientific-social journals of the XXI century. In methodological terms, it is a bibliometric study complemented with a qualitative semantic analysis. It has a non-experimental, descriptive design with longitudinal scopes. A total of 1,554 publications from three relevant journals of the Chilean social science system were analyzed between 2000 and 2019. The results show a) a structure of these symbolically generalized media under study; and b) they manage to unravel the social scientific semantics communicated in these media. It is concluded that the analyzed media are of individual writing, male, of institutional collaboration, mainly Chilean and Argentinean, with an ascending level of publications, in Spanish language, using secondary sources as documentation. In semantic terms, the media communicate a theoretical and epistemological relevance, which with methodological and essayist rigor build an identarian and situated political-social reflection. The work has a semantic and qualitative innovative potential applied to bibliometric studies of Chilean media in an important period of time, with work substantially carried out through quantitative variables, complementing from the interpretative in a semantic construction that contributes to configure an ethos of an area of study from its documentary sources.
Keywords: Social sciences system; Symbolically generalized media; Semantics; Bibliometrics